USP13: Multiple Functions and Target Inhibition - Li, Xiaolong; Yang, Ge; Zhang, Wenyao; Qin, Biying; Ye, Zifan; Shi, Huijing; Zhao, Xinmeng; Chen, Yihang; Song, Bowei; Mei, Ziqing; Zhao, Qi; Wang, Feng (Frontiers in Cell and Developmental Biology, 2022)
As a deubiquitination (DUB) enzyme, ubiquitin-specific protease 13 (USP13) is involved in a myriad of cellular processes, such as mitochondrial energy metabolism, autophagy, DNA damage response, and endoplasmic reticulum-associated degradation (ERAD), by regulating the deubiquitination of diverse key substrate proteins. Thus, dysregulation of USP13 can give rise to the occurrence and development of plenty of diseases, in particular malignant tumors. Given its implications in the stabilization of disease-related proteins and oncology targets, considerable efforts have been committed to the discovery of inhibitors targeting USP13. Here, we summarize an overview of the recent advances of the structure, function of USP13, and its relations to diseases, as well as discovery and development of inhibitors, aiming to provide the theoretical basis for investigation of the molecular mechanism of USP13 action and further development of more potent druggable inhibitors.